2022
DOI: 10.3390/ijerph19074238
|View full text |Cite
|
Sign up to set email alerts
|

Body Fat Percentage and Normal-Weight Obesity in the Chinese Population: Development of a Simple Evaluation Indicator Using Anthropometric Measurements

Abstract: Few studies explore the associations between body fat percentage (BFP) prediction and evaluation indicators for Chinese with normal-weight obesity. We aimed to explore convenient and cost-free BFP evaluation indicators to routinely monitor BFP status in Chinese patients with normal-weight obesity. Participants (N = 164) were divided into three groups according to body mass index (BMI) and BFP: normal-weight lean, normal-weight obese, and overweight and obese. Differences in body composition and circumference w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The problem relates not only to the gender and age divisions but also to the standardization of BMI values worldwide without taking into account the ethnic variation in physique caused by the climatic conditions in which the subjects live (different physiques of Central Africans, East Asians, or Northern Europeans). This is why an increasing number of authors are questioning the WHO classification of body mass abnormalities, especially in seniors or in gender comparisons ( World Health Organization Obesity, 2000 ; Deurenberg et al, 2002 ; World Health Organization Expert Consultation, 2004 ; Gupta and Kapoor, 2012 ; Bhogal and Langford, 2014 ; Chwałczyńska, 2017 ; Silva et al, 2017 ; Christensen et al, 2018 ; Mialich et al, 2018 ; Provencher et al, 2018 ; Chwałczyńska and Andrzejewski, 2021 ; Zhu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The problem relates not only to the gender and age divisions but also to the standardization of BMI values worldwide without taking into account the ethnic variation in physique caused by the climatic conditions in which the subjects live (different physiques of Central Africans, East Asians, or Northern Europeans). This is why an increasing number of authors are questioning the WHO classification of body mass abnormalities, especially in seniors or in gender comparisons ( World Health Organization Obesity, 2000 ; Deurenberg et al, 2002 ; World Health Organization Expert Consultation, 2004 ; Gupta and Kapoor, 2012 ; Bhogal and Langford, 2014 ; Chwałczyńska, 2017 ; Silva et al, 2017 ; Christensen et al, 2018 ; Mialich et al, 2018 ; Provencher et al, 2018 ; Chwałczyńska and Andrzejewski, 2021 ; Zhu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Normal BMI obesity refers to people with normal BMI and high PBF. Previous studies found this specific population was susceptible to metabolic disorders and PBF could be used to help assess the metabolic risk ( 16 18 ). Thus, it is more reliable to establish PBF as an index to assess the improvement effect of body composition in this specific population.…”
Section: Introductionmentioning
confidence: 95%
“…Obesity has emerged as a significant global health concern in recent times [ 13 ]. Extensive research has provided robust evidence establishing a linkage between obesity and an increased risk of KSD [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, studies have found that BMI is a poor predictor of body fatness due to its low sensitivity [ 19 ]. Instead, body fat percentage (BFP), defined as the ratio of total fat mass to total body mass, provides a more precise review of body fat composition [ 20 ] that may overcome the limitation of BMI [ 13 ]. In the last two decades, the World Health Organization (WHO) has recognized the discrepancy between BMI and BFP, especially in the Asian population where individuals tend to exhibit a higher BFP for the same BMI compared to other ethnicities [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation